Extraction of Flavonoids from Merremia mammosa Using Ethanol Solvent in a Fixed-Bed Column - Panut Mulyono; Alfita Sofia Yuzki; Maulid Diana Sari; Nur Rofiqoh Eviana Putri (ASEAN Journal of Chemical Engineering, 2022)
This research aims to investigate the best operating condition for the extraction process of flavonoids from Merremia mammosa root by determining the mass transfer coefficient (Ke). The root was prepared by drying, crushing, and sieving into a homogeneous size and then extracted in a fixed-bed column using 70 wt% of ethanol as a solvent for 2 hours. The obtained samples were then analyzed every 30 min using high-performance liquid chromatography. The parameters investigated in this research were particle size of 1.275, 1.85, and 4.01 mm and solvent flow rate of 3, 6, and 9 mL/s. Based on the experimental data, the value of Ke was calculated using the Hooke-Jeeves numerical method of optimization. The results showed that the decrease in particle size and the increase in solvent flow rate could increase the Ke values, leading to the high concentration of flavonoids extracted using the solvent. The Ke values obtained in this research ranged from 0.3145 m/s to 0.7880 m/s. The empirical equation that shows the correlation between Ke and the parameters can be expressed as Sh = 1.10 × 1014 Re0.0564 (1 − ε)0.8718 with a relative error of 6.13% compared with the experimental data (Sh is the Sherwood number, Re is the Reynolds number, and ε is the porosity of the fixed-bed column).